Inside the Mars rover - Baker, David, 1944- (Geek's guide to space., 2018)
Explores the history of NASA and other space agencies' exploration of Mars, covering the construction and missions of several different Mars Rovers, including Spirit and Opportunity. Showcases the technology on the Rovers and how scientists have used it to study different properties of the atmosphere and surface of Mars. Includes a glossary, index, and suggestions for further information and reading.